Regulation of Segregation of Agri-Food Flows in the EAEU Countries - Svetlana V. IVANOVA (Communications of International Proceedings, 2020)
The article is devoted to identifying global and regional trends in the segregation of agricultural flows. We are talking about the production and turnover of agricultural goods produced a) by traditional industrial intensive technology; b) using genetic modification; c) based on organic farming technologies. A conclusion is made about the world tendency of outstripping the growth of areas for sowing GM crops relative to areas of organic farming. The state, possibilities and problems of the introduction of organic farming technologies in the EAEU (Eurasian Economic Union) are investigated. The analysis of the current institutional environment for the formation of organic farming in the EAEU countries and the main regulatory acts concerning the turnover of GM products on the territory of the Union, taking into account the concepts of food security of the Russian Federation and the EAEU. According to the author, biotechnologies are a priori dual-use technologies, that is, they can be used both to the detriment and benefit of humans and the environment. The lack of evidence of the safety of GMOs (taking into account long-term effects) means the validity of maintaining the ban on the cultivation of GM crops in the territory of the EAEU countries. When importing a GM product, the precautionary principle must be followed. It is concluded that there are discrepancies in interpretations in a number of legal documents with a general trend towards convergence of the positions of the five countries.
Keywords: EAEU; institutional environment; food security.